Explaining the Variation in Empirical Estimates of Tax Elasticities of Foreign Direct Investment - Ruud A. de Mooij; Sjef Ederveen (Tinbergen Institute, 2005)
This study aims to explain the variation in empirical estimates in the literature on the elasticity of foreign direct investment with respect to company tax levels. To that end, we extend the meta analysis of De Mooij and Ederveen (2003) by considering an alternative classification of the literature, including new studies that have recently become available, and by paying more systematic attention to various control variables in primary studies. We find that the type of capital data and tax data exert a systematic impact on reported elasticities. Also controlling for openness and agglomeration tendencies appears to significantly affect the elasticity values.
Keywords: E2; F2; H2; 330; Corporate taxation; Foreign direct investment; meta analysis; semi-elasticity; Auslandsinvestition; Unternehmensbesteuerung; Steuertarif; Elastizität; Schätzung; EU-Staaten